Sizing the carbon sink associated with Posidonia oceanica seagrass meadows using very high-resolution seismic reflection imaging. (August 2021) - Monnier, Briac; Pergent, Gérard; Mateo, Miguel Ángel; Carbonell, Ramon; Clabaut, Philippe; Pergent-Martini, Christine
Abstract: Among blue carbon ecosystems, seagrass meadows have been highlighted for their contribution to the ocean carbon cycle and climate change mitigation derived from their capacity to store large amounts of carbon over long periods of time in their sediments. Most of the available estimates of carbon stocks beneath seagrass meadows are based on the analysis of short sediment cores in very limited numbers. In this study, high-resolution seismic reflection techniques were applied to obtain an accurate estimate of the potential size of the organic deposit underlying the meadows of the Mediterranean seagrass Posidonia oceanica (known as 'matte'). Seismic profiles were collected over 1380 km of the eastern continental shelf of Corsica (France, Mediterranean Sea) to perform a large-scale inventory of the carbon stock stored in sediments. The seismic data were ground-truthed by sampling sediment cores and using calibrated seismo-acoustic surveys. The data interpolation map highlighted a strong spatial heterogeneity of the matte thickness. The height of the matte at the site was estimated at 251.9 cm, being maximum in shallow waters (10–20 m depth), near river mouths and lagoon outlets, where the thickness reached up to 867 cm. Radiocarbon dates revealed the presence of seagrass meadows since the mid-Holocene (7000–9000 cal yr BP). Through the top meter of soil, the matte age was estimated at 1656 ± 528 cal yr BP. The accretion rate showed a high variability resulting from the interplay of multiple factors. Based on the surface area occupied by the meadows, the average matte thickness underneath them and the carbon content, the matte volume and total Corg stock were estimated at 403.5 ± 49.4 million m 3 and 15.6 ± 2.2 million t Corg, respectively. These results confirm the need for the application of large-scale methods to estimate the size of the carbon sink associated with seagrass meadows worldwide. Graphical abstract: Image 1 Highlights: Thickness of P. oceanica carbon sink was estimated over more 20, 424 ha in Corsica. This study is based on the use of an extensive HR seismic reflection dataset. Matte height and volume were assessed on average at 2.5 m and 404 ± 49 million m 3 . Seismic reflection method has proved valuable for large-scale carbon sink estimates.